2008
DOI: 10.1128/aac.01438-07
|View full text |Cite
|
Sign up to set email alerts
|

New Anti-Infective Coatings of Medical Implants

Abstract: Implantable devices are highly susceptible to infection and are therefore a major risk in surgery. The present work presents a novel strategy to prevent the formation of a biofilm on polytetrafluoroethylene (PTFE) grafts. PTFE grafts were coated with gentamicin and teicoplanin incorporated into different lipid-like carriers under aseptic conditions in a dipping process. Poly-D,L-lactic acid, tocopherol acetate, the diglyceride Softisan 649, and the triglyceride Dynasan 118 were used as drug carriers. The drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 30 publications
(32 reference statements)
1
37
0
2
Order By: Relevance
“…When the rate of degradation was high, then the release concentration was also found out to be high. Similar condition was experienced by Matl et al 29 during their research when they analysed the release of gentamicin and teicoplanin from PTFE vascular stents grafted with carriers like DL-lactic acid, tocopherol acetate and dynasan. Zarida et al 30 reported that the rate of release of tobramycin and gentamicin was due to the rate of degradation of the drug containing calcium phosphate beads.…”
Section: Discussionmentioning
confidence: 66%
“…When the rate of degradation was high, then the release concentration was also found out to be high. Similar condition was experienced by Matl et al 29 during their research when they analysed the release of gentamicin and teicoplanin from PTFE vascular stents grafted with carriers like DL-lactic acid, tocopherol acetate and dynasan. Zarida et al 30 reported that the rate of release of tobramycin and gentamicin was due to the rate of degradation of the drug containing calcium phosphate beads.…”
Section: Discussionmentioning
confidence: 66%
“…uncemented coated titanium disc: Gentamicinpalmitat und zahlreiche andere Antibiotika-/Antiseptikaverbindungen mit Fettsäuren wurden zwischenzeitlich mit Erfolg zur bakteriziden Ausrüstung von Implantaten wie zementloser Endoprothesen, Wirbelkörper, Zahnimplantate, Gefäßprothesen, Nahtmaterial und Knochenersatzstoffe eingesetzt [9], [7], [4], [5], [3] . In enger Kooperation von Universität und Industrie werden derzeit die Grundlagen für die humane Anwendung erarbeitet.…”
Section: Materials Und Methodeunclassified
“…Es kommt vielmehr bei den Mikro-organismen durch Quorum-Sensing zu einer Stoffwechsel-umstellung. Die Mikroorganismen wachsen nicht mehr in einer planktonischen sondern in einer sessilen Form [1,4,7], Die MHK der Bakterien in mg/1 ist dann gegenüber Antibiotika im Vergleich zum planktonischen Wachstum um das bis zu lOOOfache höher [9], Um die Biofilmbildung zu verhindern, muss daher das Anheften von Mikroorganismen an die Fremdkörper verhindert werden. Bei der systemischen intravenösen Antibiotikaprophylaxe bzw.…”
Section: Abb 1: Simulationsmodell Einer Infektion Mit Immunantwort Uunclassified
“…Recently, new lipid-based formulations to incorporate antibiotics for anti-infective action in grafts were developed. In this case, PFTE grafts were coated with lipophilic agents such as poly-lactid acid or tocopherol acetate as carriers for gentamicin and teicoplanin, in order to release high drug concentrations locally and completely inhibit bacterial colonization on the implant (Matl et al, 2008). A recent study also reported the covalent attachment of quaternary ammonium groups to stainless steel and porous filter paper (cellulose) surfaces, through low-pressure plasma-enhanced functionalization (Jampala et al, 2008).…”
Section: Wwwintechopencommentioning
confidence: 99%